Penggunaan Metode Cerita untuk Meningkatkan Keaktifan Peserta Didik dalam Bertanya, Mengemukakan Pendapat dan Menjawab Pertanyaan - Rukayah, Rukayah (Universitas Negeri Medan, 2014)
This study reveals that there is an increasing learners activity after learning by story telling method in the Kindergarten of Musara Ate, Blang Kolak 1, District of Bebesan, Central Aceh Regency, Province Aceh in 2014/2015 school year. In the beginning, there were difficulties faced by children Â in terms of speaking skills in telling information orally in learning processes. The difficulties mainly in to comment on their lessons in the classroom. Secondly, learners always confused and difficult to get inspired to speak. Third learners mostly silent when the teacher opens the question and answer session, so the level is very low speaking learners. In addition to these problems, the students lack motivation in learning noticed that interest to argue no idea who will be disclosed. This study uses action research (action research) as much as two cycles. Each round consists of four phases: design, action and observation, reflection and revision. Based on these results it can be concluded that the activities of learners per cycle increased significantly. Of the five aspects of the observations which is an indicator of student learning activities that liveliness asked, express opinions, answer questions, active in doing the task, working in groups active in most of the authors observe already mastered.